2019
DOI: 10.1111/bjh.16286
|View full text |Cite
|
Sign up to set email alerts
|

Single‐agent daratumumab in patients with relapsed and refractory multiple myeloma requiring dialysis: results of a Spanish retrospective, multicentre study

Abstract: Between 20-40% of patients with multiple myeloma (MM) present with renal impairment (RI) at diagnosis (Korbet & Schwartz, 2006; Kastritis et al., 2007) and up to 10% of them require dialysis (Dimopoulos et al., 2010). Prognosis in these patients remains significantly worse when compared with patients with normal renal function (Haynes et al., 2010). Daratumumab is an anti-CD38 IgG kappa human monoclonal antibody that has demonstrated superior clinical benefit across lines of therapy, either as monotherapy or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 16 publications
(15 reference statements)
1
25
0
Order By: Relevance
“…3 A pooled analysis of these monotherapy studies showed an overall response rate (ORR) of 31.1%, median progression-free survival (PFS) of 4.0 months, median overall survival (OS) of 20.1 months, and a manageable toxicity profile for patients treated with daratumumab at 16 mg/kg. 10 The efficacy and favorable tolerability of daratumumab monotherapy has been consistently reported from recent real-world studies performed in countries such as the United States, Korea, Poland, Spain, Italy, Russia, the United Kingdom, Hungary, and Japan, with the ORR ranging from 23% to 56.3% [11][12][13][14][15][16][17] ( Table 1).…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…3 A pooled analysis of these monotherapy studies showed an overall response rate (ORR) of 31.1%, median progression-free survival (PFS) of 4.0 months, median overall survival (OS) of 20.1 months, and a manageable toxicity profile for patients treated with daratumumab at 16 mg/kg. 10 The efficacy and favorable tolerability of daratumumab monotherapy has been consistently reported from recent real-world studies performed in countries such as the United States, Korea, Poland, Spain, Italy, Russia, the United Kingdom, Hungary, and Japan, with the ORR ranging from 23% to 56.3% [11][12][13][14][15][16][17] ( Table 1).…”
Section: Introductionmentioning
confidence: 66%
“…Salomon-Perzy nski et al 13 Cejalvo et al 14 Cook et al 15 Lovas et al 16 Iida et al 17 Present Study (Turkish Cohort)…”
Section: Characteristicmentioning
confidence: 87%
See 2 more Smart Citations
“…Of note, daratumumab as single agent was effective and safely administered, without the need of dose reduction, in 15 RRMM patients with end-stage renal disease requiring dialysis [22].…”
Section: Article Highlightsmentioning
confidence: 98%